Analisi Perairan Sungai Kenten Kabupaten Banyuasin, Sumatera Selatan: Studi Kelimpahan Makrozoobentos - Ajeng Aprilia; Novin Teristiandi; Awalul Fatiqin (Program Studi Biologi, Fakultas Sains dan Teknologi, UNIPAR JEMBER, 2023)
Macrozoobenthos are basic aquatic organisms that live above or life on the bottom of the waters. This study aims to determine the diversity, uniformity and dominance of macrozoobenthos. This research was carried out in the Kenten River, Banyuasin Regency in January-April 2022 which consisted of three sampling points and this study was taken every 2 weeks for 2 months. Sampling, samples of macrozoobenthos were taken using the Ekman grab tool, then the samples that had been taken were separated from the mud and other objects with 0.5– 1 mm, levels and offered 70% alcohol. The results of the study found that there were 3 divisions, namely the Oligochaeta, Malacostraca and Insecta divisions. Based on research conducted to enjoy the highest experience at station II with a value of 184 ind/m2 and the lowest at station III with a value of 52 ind/m2. The Diversity Index (H') ranges from 0.10-0.22. The uniformity index (E) ranges from 0.15-0.23. The dominance index (D) ranges from 0.90 to 0.95